Reciprocal attention and norm of reciprocity in blogging networks - Alexia Gaudeul; Chiara Peroni (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Bloggers devote significant time not only producing content for others to read, watch or listen to, but also paying attention to and engaging in interactions with other bloggers. We hope to throw light not only on the factors that gain bloggers significant readership and lively interactions with their audience, but also on the rules that govern their relations with others. We relate bloggers' activity with the size and structure of their network of fellow bloggers. A blogger's readership increases with his activity, while bloggers who read back proportionally fewer of their readers tend also to be more active. We find evidence that those bloggers who read back proportionally fewer of their readers have less readers than bloggers who reciprocate more, but tend to receive more comments per posts.
Keywords: D64; D85; H41; L82; L86; Z13; 330; Blogs; Bloggers; Community; Friendship; Internet; LiveJournal http://www.livejournal.com/; Reciprocity; Social Media; Social Networks; Social Norms; Web 2.0; Weblogs; Virtuelle Gemeinschaft; Web 2.0; Austauschtheorie; Soziales Netzwerk